UPAYA ORANG TUA MENGEMBANGKAN KEMAMPUAN BERBICARA PADA ANAK USIA DINI (STUDI TERHADAP ORANG TUA DI TK YAPENHA BATUNG TABA) - Syafrianis, Rahmi; Kasih, Fitria; Wira Nita, Rahma (Bimbingan dan Konseling, 2013)
The problem that would examined based on fenomena that examiner found in spacious some of the kindergarden students kaced difficulty in improving speaking skill. So, the examiner raised problems about: The parents effort to improved speaking skill for childrens (a case study at parents in Â kindergarden ). The porpose of this research are to describes: 1) The parrents effort to improve speaking skill, that vaced by the childrens speaking understanding. 2) The parents effort to improve speaking skill that vaced in children speaking skill. Kind this research used descriptive quantity method. The population of this reseach is the parents of the students class B1 and B2 in Â kindergarden Padang in 2012-2013 that some 30 people. The data collected by fill in the inquity, observation and interview, then did an analysis data with using persantase technic and narrative analise. The result reached showing that the parent effort to improve speaking skill to the childrents are. Vaced in childrents speaking skills is from respondence it also had in minus category. Base on the result resarch above, it can summaries that: parents effort to improve speaking skill to childrent it enter in minus category 50 that, hope foll to all of the studentâs parents, alls of the feachers improving the children speaking skills as good and optimal.